2021
DOI: 10.3389/fnbeh.2021.613798
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Cannabinoid Receptor Type 1 in the Brain of the Genetically Audiogenic Seizure-Prone Hamster GASH/Sal

Abstract: The endocannabinoid system modulates epileptic seizures by regulating neuronal excitability. It has become clear that agonist activation of central type I cannabinoid receptors (CB1R) reduces epileptogenesis in pre-clinical animal models of epilepsy. The audiogenic seizure-prone hamster GASH/Sal is a reliable experimental model of generalized tonic-clonic seizures in response to intense sound stimulation. However, no studies hitherto had investigated CB1R in the GASH/Sal. Although the distribution of CB1R has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 124 publications
(168 reference statements)
2
8
1
Order By: Relevance
“…Double immunofluorescence assays demonstrated a virtual complete co-localization between Af450, and Af380-immunoreactivities, but more importantly, both antibodies produced intense immunoreactivity largely restricted to axonal fibres and presynaptic-like puncta with an excellent signal-to-noise relationship in rat brain cortical sections, and the signals were virtually abolished by peptide preadsorption. This is consistent with several studies that showed a similar CB 1 immunoreactivity distribution profile using antibodies raised against C-terminal end fragments of variable length, including peptides comprising the last 13 (Egertová and Elphick 2000), 15 (Bodor et al 2005;Deshmukh et al 2007;Eggan and Lewis 2007;Eggan et al 2010) and 73 (Hájos et al 2000;Wager-Miller et al 2002;Harkany et al 2003;Monory et al 2006;Eggan and Lewis 2007) C-terminal end residues, as well as a number of reports using Af380 (Lafourcade et al 2007;Yoneda et al 2013;Diniz et al 2019;Fuerte-Hortigón et al 2021) and Af450 (Yoneda et al 2013;Rivera et al 2015;Exposito-Alonso et al 2020) antibodies in the rodent brain cortex. Moreover, both Af380 (Mateo et al 2017) and Af450 (Lafourcade et al 2007;Peñasco et al 2020;Egaña-Huguet et al 2021) antibodies have proven to be adequate to describe the ultrastructural distribution of CB 1 receptors and have been validated for specificity in transgenic mice lacking CB 1 receptor (Hebert-Chatelain et al 2014b;Remmers et al 2017;Gutiérrez-Rodríguez et al 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Double immunofluorescence assays demonstrated a virtual complete co-localization between Af450, and Af380-immunoreactivities, but more importantly, both antibodies produced intense immunoreactivity largely restricted to axonal fibres and presynaptic-like puncta with an excellent signal-to-noise relationship in rat brain cortical sections, and the signals were virtually abolished by peptide preadsorption. This is consistent with several studies that showed a similar CB 1 immunoreactivity distribution profile using antibodies raised against C-terminal end fragments of variable length, including peptides comprising the last 13 (Egertová and Elphick 2000), 15 (Bodor et al 2005;Deshmukh et al 2007;Eggan and Lewis 2007;Eggan et al 2010) and 73 (Hájos et al 2000;Wager-Miller et al 2002;Harkany et al 2003;Monory et al 2006;Eggan and Lewis 2007) C-terminal end residues, as well as a number of reports using Af380 (Lafourcade et al 2007;Yoneda et al 2013;Diniz et al 2019;Fuerte-Hortigón et al 2021) and Af450 (Yoneda et al 2013;Rivera et al 2015;Exposito-Alonso et al 2020) antibodies in the rodent brain cortex. Moreover, both Af380 (Mateo et al 2017) and Af450 (Lafourcade et al 2007;Peñasco et al 2020;Egaña-Huguet et al 2021) antibodies have proven to be adequate to describe the ultrastructural distribution of CB 1 receptors and have been validated for specificity in transgenic mice lacking CB 1 receptor (Hebert-Chatelain et al 2014b;Remmers et al 2017;Gutiérrez-Rodríguez et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Here we performed a F4P-based analysis of the specificity of five representative commercial anti-CB 1 antibodies designed against N-and C-terminal regions of CB1 receptor (hereinafter referred to as N-and C-terminal antibodies) and selected on the basis of the sequences against which they were generated, which can determine the final outcome in different end-use applications. This included two N-terminal and one C-terminal antibodies from Santa Cruz Biotechnology, which have been discontinued and replaced by other antibodies probably due to low demand, and two polyclonal antibodies raised in goat and rabbit against the 31 amino acids at the extreme carboxy-terminus (C-terminus) of CB 1 receptor, which have been widely used in the last decade (Yoneda et al 2013;Rivera et al 2015;Rodríguez-Cueto et al 2016;Mateo et al 2017;Puighermanal et al 2017;Rhomberg et al 2018;Diniz et al 2019;Puente et al 2019;Uchigashima et al 2020;Exposito-Alonso et al 2020;Peñasco et al 2020;Egaña-Huguet et al 2021;Fuerte-Hortigón et al 2021) and validated for some applications using different transgenic mice models lacking CB 1 receptor, either completely or in specific cell phenotypes or subcellular compartments (Hebert-Chatelain et al 2014a;Remmers et al 2017;Gutiérrez-Rodríguez et al 2018). To this end, our workflow combined commonly accepted testing and validation approaches along with pharmacological assays to confirm or rule out the presence of CB 1 receptor in samples yielding CB 1 -like immunoreactive bands on Western blot.…”
Section: Introductionmentioning
confidence: 99%
“…There are a multitude of examples in which increases in CB1 function have a protective effect against ear clip seizure ( 54 ), slow wave discharges ( 34 , 55 , 56 ), hyperthermia-induced seizure ( 57 ), pilocarpine models of MTLE ( 58 , 59 ), or audiogenic seizures ( 60 ). Other studies have demonstrated an increase in CB1 receptor expression following seizure in temporal lobe kindling ( 61 , 62 ), some brain regions of GASH/Sal hamsters ( 63 ), and pilocarpine models of MTLE ( 64 , 65 ), or have shown a detrimental role of CB1 agonists worsening generalized seizure activity ( 66 , 67 ). Thus, it appears that involvement of the CB1 receptor in epilepsy may depend on the type of seizure (focal vs. generalized), timeline of progression (acute vs. chronic), and type of agent used (agonist vs. modulator).…”
Section: Components Of the Endocannabinoid System In Depression And E...mentioning
confidence: 99%
“…Synthetic cannabinoids primarily interact with the endocannabinoid system, along with its G protein-coupled receptors, namely, the cannabinoid receptor type-1 and the cannabinoid receptor type-2. Tey mostly interact with the former and less with the latter [89]. Te cannabinoid receptor type-1 is widely spread in the brain, with concentrated amounts found in the basal ganglia, hippocampus, and neo-cortex, where they modulate the release of presynaptic neurotransmitter and contribute to many modulations of brain functions, including reward, memory, executive, and emotional functions [24,90].…”
Section: Action Mechanismmentioning
confidence: 99%
“…Considering this, the cannabinoid receptor type-2 was at frst believed to be restricted to peripheral tissues and immune cells but recently was found in brain stem neurons and cerebellum, where their functions have been clearly described [92]. However, how these two receptors exactly modulate the efects of synthetic cannabinoids and the exact diferences between the clinical efects of synthetic cannabinoids and traditional cannabis remain insufciently described, although recent studies suggest mitochondrial homeostasis disruption or cannabinoid receptors' biased signaling [89,93].…”
Section: Action Mechanismmentioning
confidence: 99%